A smart mobile pouch as a biomechanical energy harvester towards self-powered smart wireless power transfer applications. Issue 28 (9th May 2017) - Chandrasekhar, Arunkumar; Alluri, Nagamalleswara Rao; Sudhakaran, M. S. P.; Mok, Young Sun; Kim, Sang-Jae
Abstract : A Smart Mobile Pouch Triboelectric Nanogenerator (SMP-TENG) is introduced as a promising eco-friendly approach for scavenging biomechanical energy for powering next generation intelligent devices and smart phones. Abstract : A Smart Mobile Pouch Triboelectric Nanogenerator (SMP-TENG) is introduced as a promising eco-friendly approach for scavenging biomechanical energy for powering next generation intelligent devices and smart phones. This is a cost-effective and robust method for harvesting energy from human motion, by utilizing worn fabrics as a contact material. The SMP-TENG is capable of harvesting energy in two operational modes: lateral sliding and vertical contact and separation. Moreover, the SMP-TENG can also act as a self-powered emergency flashlight and self-powered pedometer during normal human motion. A wireless power transmission setup integrated with SMP-TENG is demonstrated. This upgrades the traditional energy harvesting device into a self-powered wireless power transfer SMP-TENG. The wirelessly transferred power can be used to charge a Li-ion battery and light LEDs. The SMP-TENG opens a wide range of opportunities in the field of self-powered devices and low maintenance energy harvesting systems for portable and wearable electronic gadgets.